Geological features within the Big Indian Lake pluton, Hants County, Nova Scotia: evidence of igneous layering from recent diamond drilling - Corey, M. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1992)
This paper describes geological features observed in diamond drill core recovered from three holes in the Big Indian Lake pluton near the eastern margin of the South Mountain Batholith. The pluton is comprised of four texturally variable granitic facies (order of decreasing abundance): (1) megacrystic to equigranular monzogranite and leuco-monzogranite, (2) porphyritic biotite monzogranite, (3) equigranular leucomonzogranite, and (4) microgranitc. Evidence of igneous layering observed in drill core includes: (1) the presence of a cumulate-like aggregate of plagioclase, (2) centimetre-thick layers modally enriched in biotite and apatite, and (3) gradational contacts between granitic rock-types. The plagioclase aggregate contains SO to 90% zoned and generally equidimensional plagioclase crystals which commonly have mutually interfering grain boundaries and a poikilitic texture characterized by abundant biotite inclusions. Contacts of the plagioclase aggregate with other facies of the pluton are generally gradational, and marked by a progressive increase in biotite and decrease in euhedral plagioclase crystals. The amount of plagioclase-rich aggregate decreases with depth in the drill core, and granodiorite and biotite monzogranite become more abundant. They grade into predominately leucomonzogranite and microgranite at depth. The microgranite is typically of syenogranite composition and closely associated with several types of alteration and mineralization. The common occurrence of pegmatite within the microgranite at boundaries with equigranular leucomonzogranite suggests that the microgranitc crystallized from a highly fractionated, water-saturated liquid. The microgranite may represent a texturally and mineralogically modified leucomonzogranite rather than a primary magmalic product. The occurrence of what appears to be primary magmatic layering in the Big Indian Lake pluton appears to confirm the relevance of applying fractional crystallization models to the South Mountain Batholith.